2020
DOI: 10.3390/antiox9020186
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients, Antinutrients, Phenolic Composition, and Antioxidant Activity of Common Bean Cultivars and their Potential for Food Applications

Abstract: Phaseolus vulgaris L. is the most commonly consumed legume in the world, given its high vegetable protein content, phenolic compounds, and antioxidant properties. It also represents one of the most sustainable, low-carbon and sources of food available at present to man. This study aims to identify the nutrients, antinutrients, phenolic composition, and antioxidant profile of 10 common bean cultivars (Arikara yellow, butter, cranberry, red kidney, navy, pinto, black, brown eyed, pink eyed, and tarrestre) from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 42 publications
6
50
0
4
Order By: Relevance
“…Taking into account all the results, the bean species collected in the Mayan region of Mexico exhibit high potential for biological activity that could be used to develop products due their nutritional, phenolic content, and their antioxidant effect could prevent some chronic diseases related to the oxidative stress [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account all the results, the bean species collected in the Mayan region of Mexico exhibit high potential for biological activity that could be used to develop products due their nutritional, phenolic content, and their antioxidant effect could prevent some chronic diseases related to the oxidative stress [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this region, rural areas with low economic resources, a lack of social assistance and information on health issues, low academic preparation, and the deep-rooted predominance of their culture, among other factors, influence the nutritional status of these communities [33]. nutritional, phenolic content, and their antioxidant effect could prevent some chronic diseases related to the oxidative stress [32].…”
Section: Plant Materialsmentioning
confidence: 99%
“…In four varieties of common beans and soybeans, catechin was reported in largest levels in soybeans but appeared in all the varieties before and after the cooking process [6]. Apart from catechin, quercetin 3-glucoside and kaempferol 3-glucoside were identified in three-fourths of bean varieties, whereas myricetin 3glucoside was present in 10% of varieties only [34]. In another study, the presence of quercetin and kaempferol 3-glucoside was reported for different bean varieties [35].…”
Section: Flavonoidsmentioning
confidence: 88%
“…Black beans and pearl beans were able to show strong AA among the studied bean varieties [69]. In another study, red kidney beans showed strongest AA (15 μmol Trolox equivalents g À1 seed dry weight), while brown-eyed bean varieties had the lowest AA (6.22 μmol Trolox equivalents g À1 seed dry weight) [34]. In the case of underutilized legume seeds, velvet bean seed had the highest AA, followed by cowpea and French bean [70].…”
mentioning
confidence: 88%
See 1 more Smart Citation